Characteristics of Fast ion beam in Neon and Argon filled plasma focus correlated with Lee Model Code - Damideh, V.; Chin, O.H.; Saw, S. H.; Lee, P. C. K.; *Lee, S. (Elsevier, 2019)
In this paper, results of time-of-flight measurements of fast ion beam generated and accelerated in the final pinch phase of a 2 kJ dense plasma focus device at 12 kV in Neon and Argon are presented. The measurements were made using a 50 Ω F Cup and these results were correlated with Lee Model Code computations. The results include fast ion beam properties such as ion speed, energy, flux and fluence at 2–4 Torr Neon and 0.5–1.5 Torr Argon. Ion signals with FWHM minimum values of 42 ns and 47 ns respectively for 2.5 Torr Neon and 0.9 Torr Argon were measured. The maximum most common ion energy of 450 ± 30 keV at 2.5 Torr Neon and 1230 ± 90 keV at 0.9 Torr Argon were measured. Ion time-of-flight measurements including ion speed and energy, ion flux, ion fluence by Faraday Cup show very consistent correlation with Lee Model Code results for Neon and Argon. This paper validates the computation of plasma focus ion beam properties by the Lee Code.